Improvement of Didactic Competences of the Technology Teacher - Ishmuradova Gulbaxor Izmuradovna; Kaxxarova Tozagul Abdimuminovna (Periodica Journal, 2023)
In this article, the theoretical analysis of the concepts of "Pedagogical" and "didactic" competence of the teacher, the main levels of didactic competence are shown. Didactic competence is one of the components of professional competence. Also, the content, level and fields of qualifications that are part of didactic competence are also described
Keywords: competence; creativity; reproductive; didactic competence; heuristic; technological education